2019
DOI: 10.3390/su11051325
|View full text |Cite
|
Sign up to set email alerts
|

A Markov Regime Switching Approach towards Assessing Resilience of Romanian Collective Investment Undertakings

Abstract: This paper explores the sensitivity of Romanian collective investment undertakings’ returns to changes in equity, fixed income and foreign exchange market returns. We use a sample of 80 open-end investment funds and pension funds with daily returns between 2016 and 2018. Our methodology consists of measuring changes in the daily conditional volatility for the fund returns (EGARCH) and changes in their conditional correlation with selected market risk factors (DCC MV-GARCH) throughout different volatility regim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Similar to Badea et al [41], we labeled the volatility regimes at each period by transforming the time series of probabilities resulting from the model into the time series of volatility regimes. The labels were set as chronological binary values: 1 if the respective equity index was manifesting a high volatility and 0 if the volatility regime was a quiet one.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to Badea et al [41], we labeled the volatility regimes at each period by transforming the time series of probabilities resulting from the model into the time series of volatility regimes. The labels were set as chronological binary values: 1 if the respective equity index was manifesting a high volatility and 0 if the volatility regime was a quiet one.…”
Section: Methodsmentioning
confidence: 99%
“…The labels were set as chronological binary values: 1 if the respective equity index was manifesting a high volatility and 0 if the volatility regime was a quiet one. As Badea et al [41] propose, the rules that we used to derive the values of 0 and 1 were the following:…”
Section: Methodsmentioning
confidence: 99%
“…These show that the level of market return dispersions significantly influences the direction of fund performance more in the bearish regime than in the bullish regime of the market. However, in an analysis of fund performance determinants with Markov switching models, Badea et al (2019) found that the effect of market risk on fund performance is generally minimal in unchanging market conditions, although they found evidence of a link between the direction of general market returns and individual fund performance.…”
Section: Cross-sectional Analysis Of the Most Significant Explanatory Variablesmentioning
confidence: 99%
“…The authors are familiar with only one paper in the relevant Polish (cf. Włodarczyk and Skrodzka, 2013) and one Romanian (Badea et al, 2019) literature analyzing efficiency of a limited number of local investment funds. Therefore, this study tries to fill the existing research gap and provides an opportunity to verify the potential market anomalies in developing economies, which might differ from the ones encountered in developed ones.…”
Section: Previous Researchmentioning
confidence: 99%